2017
DOI: 10.1002/2016jb013682
|View full text |Cite
|
Sign up to set email alerts
|

Efficient inversion and uncertainty quantification of a tephra fallout model

Abstract: An efficient and effective inversion and uncertainty quantification approach is proposed for estimating eruption parameters given a data set collected from a tephra deposit. The approach is model independent and here is applied using Tephra2, a code that simulates advective and dispersive tephra transport and deposition. The Levenburg‐Marquardt algorithm is combined with formal Tikhonov and subspace regularization to invert eruption parameters; a linear equation for conditional uncertainty propagation is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 34 publications
(55 reference statements)
1
46
1
Order By: Relevance
“…We finally stress the value of combining particle transport modeling with detailed deposit observations, including not only mass depositional patterns on the ground but also detailed studies of grain shape, size, density, and, importantly, direct measurement of Vt s. Finally, we emphasize that including grain size—and not solely the mass—model evaluation of fallout deposits is necessary to fully assess the quality of the sedimentation scheme. Recent modeling work has shown that such approach reduces the uncertainty on the simulation results (White et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We finally stress the value of combining particle transport modeling with detailed deposit observations, including not only mass depositional patterns on the ground but also detailed studies of grain shape, size, density, and, importantly, direct measurement of Vt s. Finally, we emphasize that including grain size—and not solely the mass—model evaluation of fallout deposits is necessary to fully assess the quality of the sedimentation scheme. Recent modeling work has shown that such approach reduces the uncertainty on the simulation results (White et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we emphasize that including grain size-and not solely the mass-model evaluation of Journal of Geophysical Research: Solid Earth 10.1002/2017JB014412 fallout deposits is necessary to fully assess the quality of the sedimentation scheme. Recent modeling work has shown that such approach reduces the uncertainty on the simulation results (White et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the variable data quality of different tephra deposits makes it hard to come up with an universal solution. A generalized way of estimating eruption parameters, including the vent position, is to combine inverse methods with tephra transportation models (e.g., Connor and Connor, 2006;Volentik et al, 2010;Bonasia et al, 2010;Klawonn et al, 2012;Burden et al, 2013;Kawabata et al, 2013;White et al, 2017). Although sensitivity analyses have been done to these models (Scollo et al, 2008;Bonadonna et al, 2015;Pouget et al, 2016), their highdimensional parameter space could still introduce uncertainties to the problem.…”
Section: Introductionmentioning
confidence: 99%